Guidelines for the prevention, detection and management of the renal complications of COVID-19 in Africa - Elsayed, Hesham M; Wadee, Shoyab; Zaki, Mohamad S; Were, Anthony JO; Ashuntantang, Gloria E; Bamgboye, Ebun L; Davids, Mogamat Razeen; Hafez, Mohamed H; Mahamat, Maimouna; Naicker, Saraladevi; et al. (African Journal of Nephrology, 2020)
Africa trails the rest of the world in COVID-19 cases and deaths. However, as the pandemic spreads through the continent, we expect increases in community infection in the months ahead. Patients with kidney infection, especially those with end-stage kidney disease and those with kidney transplants, are at high risk for acquiring the disease and dying from it. While there is limited evidence for the benefit of interventions, we have the advantage of learning from the experiences of those in China, Europe and the Americas. This document sets forth guidance for dealing with our patients who have acute and chronic kidney disease, including those on renal replacement therapy and the staff involved in their care. Emphasis is placed on preparedness and prevention strategies. As evidence and experience accumulate, it is likely that updated guidance will be needed. L’Afrique suit le reste du monde en termes de nombre de cas et de décès dus à COVID-19. Cependant, alors que la pandémie se propage à travers le continent, nous prévoyons une augmentation de l’infection communautaire dans les mois à venir. Les patients atteints d’une maladie rénale, en particulier ceux atteints d’une maladie rénale chronique en phase terminale et ceux ayant subi une transplantation rénale, courent un risque élevé de contracter la maladie et d’en mourir. Bien que les preuves d’interventions soient limitées, nous avons l’avantage de tirer des enseignements des expériences de ceux qui se trouvent en Chine, en Europe et dans les Amériques. Ce document présente des conseils pour traiter nos patients atteints d’insuffisance rénale aiguë et chronique, y compris ceux sous thérapie de suppléance rénale et le personnel impliqué dans leurs soins. L’accent est mis sur les stratégies de préparation et de prévention. Au fur et à mesure que les preuves et l’expérience s’accumulent, il est probable que des directives actualisées seront nécessaires.